2020
DOI: 10.1002/fsn3.1368
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Pachira aquatica oil and Platonia insignis almond in cookies: Physicochemical and sensorial aspects

Abstract: The Pachira aquatica (PA) Aubl. (Malvaceae), commonly known as munguba, castanheira, wild cocoa, and maranhão nut, is a native tree of Mexico (Paula, Cruz, & Barbosa, 2006). In Brazil, it is common in the Amazon region and occurs mainly in streams and rivers, from which originated its scientific name. Some studies have shown that PA seeds present a high amount of lipids (44%), 12.9% of protein showing a high amount of essential amino acids such as tyrosine,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These results could be due to the chemical composition of amaranth containing unsaturated and saturated FAs, and the most abundant FA is linoleic acid, which comprises approximately 40% of all FAs, followed by oleic acid [ 34 ]. A study showed that the use of Platonia insignis nuts as an ingredient in the preparation of cookies reported 43.48 ± 0.37 % of oleic acid and 11.14 ± 0.15% of linolenic acid [ 35 ]. Another study also reported the presence of these FAs in cookies by the addition of flax seeds, which contained 4.75–5.31% of linolenic acid [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results could be due to the chemical composition of amaranth containing unsaturated and saturated FAs, and the most abundant FA is linoleic acid, which comprises approximately 40% of all FAs, followed by oleic acid [ 34 ]. A study showed that the use of Platonia insignis nuts as an ingredient in the preparation of cookies reported 43.48 ± 0.37 % of oleic acid and 11.14 ± 0.15% of linolenic acid [ 35 ]. Another study also reported the presence of these FAs in cookies by the addition of flax seeds, which contained 4.75–5.31% of linolenic acid [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Native from the Amazon forest, PA can be reported from southern Mexico to the north of Brazil and is mostly used in urban landscaping, restoration of wetlands, and degraded soils and forests (JORGE & LUZIA, 2012;. The PA tree produces seeds rich in lipids with high productivity which present potential for exploration for foods, pharmaceuticals, medicine, cosmetics and biofuels industries (JORGE & LUZIA, 2012;SILVA et al, 2015;RAISER et al, 2018;OLIVEIRA et al, 2019;RODRIGUES et al, 2019;SILVA et al, 2020;.…”
Section: Forestry Sciencementioning
confidence: 99%
“…Monguba is a fruit species that can be found from Southern Mexico to northern Brazil. Its fruits are similar to cocoa and the seeds have nutritional potential because they contain many proteins, lipids, and minerals, being widely studied as unconventional food plants (UFPs) (Silva et al 2020). The seed is also applicable as a biological controller due to the ethanolic extract that composes them, the oil obtained from the seeds can be used as an antioxidant and in biofuel production, and the leaves can be consumed as medicinal herbs (Pantoja et al 2020;Rodrigues et al 2019).…”
Section: Introductionmentioning
confidence: 99%